2023
DOI: 10.1002/fsn3.3419
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, antioxidant capacity, and α‐amylase and α‐glucosidase inhibitory activity of ethanol extracts of perilla seed meal

Abstract: Perilla frutescens is a medicinal herb that is commonly cultivated in Asian countries. Perilla seed is extensively pressed for cooking oil extraction. However, phenolic chemicals are still abundant in pressed perilla seed meal (PSM), which was previously thought to be useless after oil extraction. In our study, PSM was extracted using five solvents (water and 25%, 50%, 75%, and 100% ethanol) based on different ethanol concentrations, and its antioxidant activity, phenolic compounds, and inhibitory effects agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Additionally, Choi et al reported that the 75% ethanol extract from Perilla frutescens seed meal exhibited significant inhibition against α-glucosidase with IC 50 values of 361.28 ± 2.01 µg/mL. This was comparable to the IC 50 value of the positive control acarbose, which was 184.90 ± 23.23 µg/mL [23].…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, Choi et al reported that the 75% ethanol extract from Perilla frutescens seed meal exhibited significant inhibition against α-glucosidase with IC 50 values of 361.28 ± 2.01 µg/mL. This was comparable to the IC 50 value of the positive control acarbose, which was 184.90 ± 23.23 µg/mL [23].…”
Section: Introductionmentioning
confidence: 87%
“…Seed extraction for AOA, TPC, and TFC evaluation was achieved following previously described methods [31,32]. Briefly, for each replicate, 0.5 g of seeds were extracted for 4 h (constant shaking in darkness) with 5 mL 80% ethanol.…”
Section: Assessment Of Total Phenolic (Tpc) and Flavonoid (Tfc) Conte...mentioning
confidence: 99%
“…The TFC and TPC were analyzed according to the methods of Choi et al [32]. Regarding the TPC, 400 µL dH 2 O and 100 µL Folin-Ciocalten reagent were added to 100 µL of seed extract, mixed well, and left for 6 min.…”
Section: Assessment Of Total Phenolic (Tpc) and Flavonoid (Tfc) Conte...mentioning
confidence: 99%
“…Seed samples (0.5 g) were extracted with 5 mL 80% ethanol (constant shaking in darkness) for 4 h, followed by centrifugation at 5000 g for 15 min [26,27]. The supernatants were collected, filtered, completed to 5 mL with 80% ethanol, and stored at −20 • C for further analyses within a period of one week.…”
Section: Evaluation Of Total Phenolic (Tpc) and Flavonoid (Tfc) Contentsmentioning
confidence: 99%
“…The supernatants were collected, filtered, completed to 5 mL with 80% ethanol, and stored at −20 • C for further analyses within a period of one week. The TPC and TFC were evaluated per the method outlined by Choi et al [27]. For the TPC, 100 µL of each seed extract was mixed with 400 µL dH 2 O and 100 µL Folin-Ciocalten reagent.…”
Section: Evaluation Of Total Phenolic (Tpc) and Flavonoid (Tfc) Contentsmentioning
confidence: 99%